2021
DOI: 10.3389/ffgc.2021.676691
|View full text |Cite
|
Sign up to set email alerts
|

Recent Carbon Storage and Burial Exceed Historic Rates in the San Juan Bay Estuary Peri-Urban Mangrove Forests (Puerto Rico, United States)

Abstract: Mangroves sequester significant quantities of organic carbon (C) because of high rates of burial in the soil and storage in biomass. We estimated mangrove forest C storage and accumulation rates in aboveground and belowground components among five sites along an urbanization gradient in the San Juan Bay Estuary, Puerto Rico. Sites included the highly urbanized and clogged Caño Martin Peña in the western half of the estuary, a series of lagoons in the center of the estuary, and a tropical forest reserve (Piñone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 70 publications
1
20
0
Order By: Relevance
“…It may be argued that in mature, isolated mangrove systems, nutrient recycling may be of greater significance than allochthonous inputs (Twilley and Day, 1999;Alongi et al, 2004;Marchand et al, 2006). Some of the highest measures of N storage and accumulation (this study) as well as C storage were observed in the poorly flushed, least urbanized, Piñones Forest (Wigand et al, 2021). Elevated porewater NH 4…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…It may be argued that in mature, isolated mangrove systems, nutrient recycling may be of greater significance than allochthonous inputs (Twilley and Day, 1999;Alongi et al, 2004;Marchand et al, 2006). Some of the highest measures of N storage and accumulation (this study) as well as C storage were observed in the poorly flushed, least urbanized, Piñones Forest (Wigand et al, 2021). Elevated porewater NH 4…”
Section: Discussionmentioning
confidence: 63%
“…; δ 15 N = −4.52 ) and USGS 41 (δ 13 C = 37.63 ; δ 15 N = 47.57 ) were used to normalize isotopic values of working standards (blue mussel homogenate) to the air (δ15N) and Vienna Pee Dee Belemnite (δ 13 C) scales (Paul et al, 2007). Analysis of carbon storage and dominant carbon sources to the SJBE mangrove soils determined from these same cores were reported earlier (Eagle et al, 2021;Wigand et al, 2021).…”
Section: Processing For Percent C N and Stable Isotopesmentioning
confidence: 93%
See 1 more Smart Citation
“…The two main inputs were mangrove forest primary production and net DIC production in mangrove soils to a depth of 1 m. The latter is not usually considered in carbon mass balance estimates, but evidence suggests that centuries-old, sequestered carbon is still susceptible to remineralization and tidal DOC and DIC export [47], supporting the idea that organic carbon deposited prior to mangrove colonization continues to be decomposed as all mangroves colonize intertidal flats that have considerable stores of C ORG [1]. This idea is supported by the fact that radiocarbon dating of mangrove soil profiles of the upper 1-3 m [32,34,[38][39][40] indicate subsurface mangrove deposits that are centuries-old, and certainly older that the existing mangrove vegetation. Another unqualified pathway is groundwater which can in many locations provide significant quantities of carbon-and nutrient-rich subsurface water [6].…”
Section: Inputsmentioning
confidence: 98%
“…Rates of carbon sequestration in mangrove forests average 183.6 g C ORG m −2 a −1 (1 SE = 14.7 g C ORG m −2 a −1 ) with a median of 114.8 g C ORG m −2 a −1 and a very wide range from 0.001 to 1722.2 g C ORG m −2 a −1 (data in Alongi [8] updated with additional refs. [9,28,[32][33][34][35][36][37][38][39][40]). More than half of all measurements were <100 g C ORG m −2 a −1 with the highest rates observed in degraded or heavily impacted, disturbed forests and catchments such as in China, South and Southeast Asia, and Africa.…”
Section: Carbon Burial Ratesmentioning
confidence: 99%